Effects of Body Position and Hypovolemia on the Regional Distribution of Pulmonary Perfusion During One-Lung Ventilation in Endotoxemic Pigs - Wittenstein, Jakob; Scharffenberg, Martin; Ran, Xi; Zhang, Yingying; Keller, Diana; Tauer, Sebastian; Theilen, Raphael; Chai, Yusen; Ferreira, Jorge; Müller, Sabine; Bluth, Thomas; Kiss, Thomas; et al. (Frontiers in Physiology, 2021)
Background: The incidence of hypoxemia during one-lung ventilation (OLV) is as high as 10%. It is also partially determined by the distribution of perfusion. During thoracic surgery, different body positions are used, such as the supine, semilateral, lateral, and prone positions, with such positions potentially influencing the distribution of perfusion. Furthermore, hypovolemia can impair hypoxic vasoconstriction. However, the effects of body position and hypovolemia on the distribution of perfusion remain poorly defined. We hypothesized that, during OLV, the relative perfusion of the ventilated lung is higher in the lateral decubitus position and that hypovolemia impairs the redistribution of pulmonary blood flow. Methods: Sixteen juvenile pigs were anesthetized, mechanically ventilated, submitted to a right-sided thoracotomy, and randomly assigned to one of two groups: (1) intravascular normovolemia or (2) intravascular hypovolemia, as achieved by drawing ~25% of the estimated blood volume (n = 8/group). Furthermore, to mimic thoracic surgery inflammatory conditions, Escherichia coli lipopolysaccharide was continuously infused at 0.5 μg kg−1 h−1. Under left-sided OLV conditions, the animals were further randomized to one of the four sequences of supine, left semilateral, left lateral, and prone positioning. Measurements of pulmonary perfusion distribution with fluorescence-marked microspheres, ventilation distribution by electrical impedance tomography, and gas exchange were then performed during two-lung ventilation in a supine position and after 30 min in each position and intravascular volume status during OLV. Results: During one-lung ventilation, the relative perfusion of the ventilated lung was higher in the lateral than the supine position. The relative perfusion of the non-ventilated lung was lower in the lateral than the supine and prone positions and in semilateral compared with the prone position. During OLV, the highest arterial partial pressure of oxygen/inspiratory fraction of oxygen (PaO2/FIO2) was achieved in the lateral position as compared with all the other positions. The distribution of perfusion, ventilation, and oxygenation did not differ significantly between normovolemia and hypovolemia. Conclusions: During one-lung ventilation in endotoxemic pigs, the relative perfusion of the ventilated lung and oxygenation were higher in the lateral than in the supine position and not impaired by hypovolemia.